Form as Thought - Éric Lapierre (Museum, Materials and Discussions)
As former chief curator of the fifth Lisbon Triennial of architecture in 2019, I will first discuss about utility of such events to allow architecture to meet a wider audience as the academic or professional ones. This issue is also about form of such events in terms of overall organizations: didactic exhibitions conceived by curators vs. conceptual installations made by architects. I will explain why I chose the first option in Lisbon, and how this choice influenced the form of the exhibitions. Additionally, I will explore in which way the fact that I was an “intellectual practitioner” allowed me to give specific answers to a series of questions regarding architecture itself but as well the art of exhibition: in which way form can improve thought.